Further investigation of endothelium-derived hyperpolarizing factor (EDHF) in rat hepatic artery: studies using 1-EBIO and ouabain - Edwards, G (1999)
1. The characteristics of endothelium-dependent hyperpolarization in rat hepatic artery have been further investigated in the presence of inhibitors of cyclo-oxygenase and nitric oxide synthase. 2. Using sharp micro-electrodes, the smooth muscle hyperpolarization induced by acetylcholine, KCl or 1-ethyl-2-benzimidazolinone (1-EBIO) in intact hepatic arteries was abolished by 30 μM barium plus 500 nM ouabain. 3. In vessels without endothelium, the smooth muscle hyperpolarization induced by KCl was not reduced by 30 μM barium alone. However, in the presence of barium the effects of KCl were partially inhibited by 100 nM ouabain and essentially abolished by 500 nM ouabain. 4. Using sharp micro-electrodes, the hyperpolarization of both the smooth muscle and the endothelium induced by 1-EBIO or by acetylcholine was unaffected by 100 nM iberiotoxin. However, in the presence of 100 nM charybdotoxin, the effects of 1-EBIO were abolished whereas those of acetylcholine were only partially reduced. The hyperpolarization induced by levcromakalim was unaffected by either charybdotoxin or iberiotoxin. 5. Under whole-cell patch-clamp recording conditions, 1-EBIO induced a voltage-insensitive, charybdotoxin-sensitive K(+) current in cultured endothelial cells but was without effect on K(+) currents in smooth muscle cells isolated from hepatic arteries. 6. It is concluded that the endothelium-dependent hyperpolarization of smooth muscle induced by either acetylcholine or by 1-EBIO in rat hepatic artery is initially associated with the opening of endothelial calcium-sensitive K(+)-channels insensitive to iberiotoxin. The resulting accumulation of K(+) in the myoendothelial space activates an isoform of Na(+)/K(+)-ATPase which is sensitive to low concentrations of ouabain.